Evaluation of myocardial gene expression profiling for superior diagnosis of idiopathic giant-cell myocarditis and clinical feasibility in a large cohort of patients with acute cardiac decompensation - Escher, Felicitas; Pietsch, Heiko; Aleshcheva, Ganna; Wenzel, Philip; Fruhwald, Friedrich; Stumpf, Christian; Westermann, Dirk; Bauersachs, Johann; Enseleit, Frank; Ruschitzka, Frank; Naegele, Herbert; Laugwitz, Karl-Ludwig; et al. (Journal of Clinical Medicine, 2020)
Aims: The diagnostic approach to idiopathic giant-cell myocarditis (IGCM) is based on identifying various patterns of inflammatory cell infiltration and multinucleated giant cells (GCs) in histologic sections taken from endomyocardial biopsies (EMBs). The sampling error for detecting focally located GCs by histopathology is high, however. The aim of this study was to demonstrate the feasibility of gene profiling as a new diagnostic method in clinical practice, namely in a large cohort of patients suffering from acute cardiac decompensation. Methods and Results: In this retrospective multicenter study, EMBs taken from n = 427 patients with clinically acute cardiac decompensation and suspected acute myocarditis were screened (mean age: 47.03 ± 15.69 years). In each patient, the EMBs were analyzed on the basis of histology, immunohistology, molecular virology, and gene-expression profiling. Out of the total of n = 427 patient samples examined, GCs could be detected in 26 cases (6.1%) by histology. An established myocardial gene profile consisting of 27 genes was revealed; this was narrowed down to a specified profile of five genes (CPT1, CCL20, CCR5, CCR6, TLR8) which serve to identify histologically proven IGCM with high specificity in 25 of the 26 patients (96.2%). Once this newly established profiling approach was applied to the remaining patient samples, an additional n = 31 patients (7.3%) could be identified as having IGCM without any histologic proof of myocardial GCs. In a subgroup analysis, patients diagnosed with IGCM using this gene profiling respond in a similar fashion to immunosuppressive therapy as patients diagnosed with IGCM by conventional histology alone. Conclusions: Myocardial gene-expression profiling is a promising new method in clinical practice, one which can predict IGCM even in the absence of any direct histologic proof of GCs in EMB sections. Gene profiling is of great clinical relevance in terms of a) overcoming the sampling error associated with purely histologic examinations and b) monitoring the effectiveness of therapy.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Endomyocardial biopsy; Gene-expression profiling; Idiopathic giant-cell myocarditis